The Effect Of Asset And Liability Management On Stability And Profitability In Islamic Banks - Darmawan, Darmawan; Qodhari, Dafelia (Universitas Bangka Belitung, 2025)
This study examines the relationship between Asset Liability Management (ALM) and the stability and profitability of Islamic banks. The research aims to evaluate the impact of ALM while identifying challenges and opportunities within Islamic banking. ALM is represented by Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR), while stability and profitability are assessed through Capital Adequacy Ratio (CAR) and Return on Assets (ROA), respectively. Employing a quantitative approach, this research uses time-series data from 2013–2022, analysed through multiple linear regression with E-views software. Results indicate that NPF and FDR significantly negatively impact CAR, while NPF negatively and significantly affects ROA. Conversely, FDR shows a positive but insignificant effect on ROA. These findings highlight the critical role of efficient asset and liability management in maintaining financial stability and enhancing profitability. Islamic banks can leverage these insights to improve credit risk management and liquidity strategies. Policymakers are encouraged to refine regulations that support sustainable and Sharia-compliant banking practices.